Restorative Justice as an Alternative to Criminalization? - Ptacek, James (2014)
This paper will review the evaluation research on restorative justice (RJ) in cases of intimate partner violence. What do we know about how well RJ ensures the safety and immediate needs of survivors? What do we know about how well survivors feel a sense of justice as a result of these practices? What do we know about the ability of these practices to hold offenders accountable, and to prevent further offending